Does early improvement in depressive symptoms predict subsequent remission in patients with depression who are treated with duloxetine? - Sueki A; Suzuki E; Takahashi H; Ishigooka J (Neuropsychiatric Disease and Treatment, 2016)
Akitsugu Sueki, Eriko Suzuki, Hitoshi Takahashi, Jun Ishigooka Department of Neuropsychiatry, Tokyo Women’s Medical University, Tokyo, Japan Purpose: In this prospective study, we examined whether early reduction in depressive symptoms predicts later remission to duloxetine in the treatment of depression, as monitored using the Montgomery–Asberg Depression Rating Scale (MADRS). Patients and methods: Among the 106 patients who were enrolled in this study, 67 were included in the statistical analysis. A clinical evaluation using the MADRS was performed at weeks 0, 4, 8, 12, and 16 after commencing treatment. For each time point, the MADRS total score was separated into three components: dysphoria, retardation, and vegetative scores. Results: Remission was defined as an MADRS total score of ≤10 at end point. From our univariate logistic regression analysis, we found that improvements in both the MADRS total score and the dysphoria score at week 4 had a significant interaction with subsequent remission. Furthermore, age and sex were significant predictors of remission. There was an increase of approximately 4% in the odds of remission for each unit increase in age, and female sex had an odds of remission of 0.318 times that of male sex (remission rate for men was 73.1% [19/26] and for women 46.3% [19/41]). However, in the multivariate model using the change from baseline in the total MADRS, dysphoria, retardation, and vegetative scores at week 4, in which age and sex were included as covariates, only sex retained significance, except for an improvement in the dysphoria score. Conclusion: No significant interaction was found between early response to duloxetine and eventual remission in this study. Sex difference was found to be a predictor of subsequent remission in patients with depression who were treated with duloxetine, with the male sex having greater odds of remission. Keywords: antidepressant, early response, sex difference, serotonin–noradrenalin reuptake inhibitor